Proliferative, degradative smooth muscle cells promote aortic disease - Hulsmans, Maarten (J Clin Invest, 2020)
Aneurysms are common in the abdominal and thoracic regions of the aorta and can cause death due to dissection or rupture. Traditionally, thoracic aortic aneurysms have been labeled as a degenerative disease, characterized by alterations in extracellular matrix and loss of smooth muscle cells (SMCs) in the medial layer of the aortic wall. In this issue of the JCI, Li and colleagues introduce an unconventional concept by demonstrating that mTOR-dependent proliferative SMCs render the aortic wall vulnerable to dilatation and dissection rather than prevent disease progression. These vascular SMCs, termed degradative SMCs, compromise the medial properties and function of the aortic wall by enhanced proteolytic and phagocytic activity; however, the cells do not transdifferentiate into macrophages. The degradative SMC phenotype also worsens atherosclerotic disease and could thus be considered as a therapeutic target for diverse aortic diseases.